ORF30 and ORF34 Are Essential for Expression of Late Genes in Murine Gammaherpesvirus 68 - Wu, Ting-Ting (American Society for Microbiology (ASM), 2009)
A hallmark of productive infection by DNA viruses is the coupling of viral late gene expression to genome replication. Here we report the identification of open reading frame 30 (ORF30) and ORF34 as viral trans factors crucial for activating late gene transcription following viral DNA replication during lytic infection of murine gammaherpesvirus 68 (MHV-68). The mutant virus lacking either ORF30 or ORF34 underwent normal DNA replication but failed to express viral late gene transcripts, leading to nonproductive infection. In a reporter assay system, ORF30 and ORF34 were required for MHV-68 to activate the viral late gene promoters. Furthermore, studies using chromatin immunoprecipitation assays showed that the recruitment of RNA polymerase II to the viral late promoters during lytic infection was significantly reduced in the absence of ORF30 or ORF34. Together, the results suggest that ORF30 and ORF34 may play an important role in the assembly of the transcription initiation complex at the late gene promoters. Our discovery of the viral mutants that uncouple late gene transcription from DNA replication lays an important foundation to dissect the mechanism of this critical step of gene expression regulation.